Items Wrongfully Seized in Corruption Cases - Tirtakusuma, Andreas Eno (Journal of Law and Humanity Studies, 2025)
This paper examines the legal mechanism for third parties to file objections to the wrongful seizure of items, focusing on the applicability of Supreme Court Regulation (PERMA) No. 2 of 2022. The approaches used include legislative, case-based, and conceptual approaches. The Djoko Susilo case serves as a concrete example, where the defendant's family filed an objection to the seizure of assets that were not proceeds of a crime. PERMA No. 2 of 2022 provides a procedure for filing objections in an orderly, swift, and cost-free manner, while avoiding overlap between civil and administrative jurisdictions. However, the success of the objection is heavily dependent on proving the "good faith" of the third party, a concept that in practice is often subject to multiple interpretations and prone to misuse. This PERMA has unified legal interpretations, provided legal certainty, and strengthened the protection of ownership rights of third parties not involved in criminal activities, although the element of "good faith" remains a crucial point in determining whether the objection request will be granted by the judge. This concept needs to be clarified normatively to prevent legal ambiguity and ensure the principle of substantive justice in criminal law enforcement, particularly in corruption cases involving property.